TRANSFORMATIVE ENTREPRENEURS : HOW WALT DISNEY, STEVE JOBS, MUHAMMAD YUNUS, AND OTHER INNOVATORS SUCCEEDED - Harris, Jeffrey A., 1955- (Palgrave Macmillan, 2012)
Meticulously researched with fresh insights into the entrepreneurial process, Jeffrey Harris brings the in-depth perceptions from his nearly thirty years of venture capital experience to provide a thorough understanding of the transformative ideas and leadership abilities that separate the winners and losers